Local Wisdom on Kaili Society Expressions - St. Rahmah (Balai Bahasa Sulawesi Tengah, 2013)
Kaili society expression contains a lot of wisdom. Local wisdom is supposed to be the foundations of society in addressing the multidimensional crisis Kaili which has happened lately. In these expressions also contain cultural codes associated with their beliefs and values which is contained solidarity to build a strong unity and humanity in order to create a real togetherness. The purpose of this study was to reveal the values of local wisdom which is contained in the expression.The method which is used in this research is the study of literature, descriptive analytic, and presentation of the narrative. In the result, it is showed that local knowledge which is contained in the Kaili, very diverse, including (1) the wisdom of local communities related to the human being as an individual such as responsibility, hard work, self-awareness, politeness, and vigilance, wisdom. (2) relating to indigenous people as members of society, and (3) local knowledge relating to man as a creature of God. Developing and fostering local cultural values or wisdom in the proverb is one alternative that can be taken to mitigate the conflict that has been going on in the community of Kaili.